Photomolecular Sensor: All‐Optical Polarization‐Controlled Nanosensor Switch Based on Guided‐Wave Surface Plasmon Resonance via Molecular Overtone Excitations in the Near‐Infrared (Advanced Optical Materials 19/2020). Issue 19 (5th October 2020) - Karabchevsky, Alina; Hazan, Adir; Dubavik, Aliaksei
Abstract : Semiconductor transistor‐sensors are considered the most widely manufactured device in history. Being invented to switch electronic signals they revolutionized electronics. However, electric switches are hampered by damage from very brief electrical and thermal effects or electromagnetic interference. In article number 2000769, Alina Karabchevsky and her team from the School of ECE at Ben‐Gurion University report a revolutionary all‐optical sensor switch, engineered to operate at telecommunication wavelengths, caused by the excitation of molecular overtones in a unique hybrid plasmonic–dielectric configuration.